Complex Circles of Partition and the Asymptotic Binary Goldbach Conjecture - Agama, Theophilus; Gensel, Berndt (My University, 2022)
In this work, we continue the complex circle of partition development that was started in our foundational study [3]. With regard to command its embedding circle, we define interior and exterior points. On this foundation, we expand the concept of point density, established in [2], to include complex circles of partition. We propose the idea of a quotient complex circle of partition and investigate some of its features in analogy to the quotient group in group theory. With this notion, we can prove an asymptotic version of the Binary Goldbach Conjecture
Keywords: interior point; exterior point; Bertrand postulate; prime number theorem; asymptotic